Monitoring urban carbon dioxide emissions from the atmosphere: insights from vertical tower observations in Beijing, China - Kewei Liu; Wudi Cao; Mingming Zhu; Zifa Wang; Fei Hu; Lin Wu; Xueling Cheng (Atmospheric Environment, 2026)

Tourism-associated shifts in predicted microbial carbon-processing capacity and implications for carbon dynamics in urban wetlands: insights from Xixi National Wetland Park, China - Tianle Yu; Kewei Xu; Renzhang Lin; Zhenmei Lu; Yongge Sun (Wetlands Ecology and Management, 2026)

First report of a pseudorabies virus in porcupines: Genomic characterization of a recombinant strain and safety assessment of the Bartha-K61 vaccine - Nana Yan; Jingru Xu; Lin Zheng; Sisi Fan; Hui Guo; Yue Qi; Xinling Lai; Yaoming You; Kaixin Zhang; Jingxue Liu; Jiankui Liu; Ailing Dai; et al. (Veterinary Microbiology, 2026)

Anomaly analysis and comprehensive evaluation of geochemical exploration for oil and gas in the Lindian area, Northern Songliao Basin - Xiaohui Lin; Fazhun Rong; Kewei Xu; Yu Zou; Wu Li; Yinjie Chen (Geosciences Journal, 2026)

Optimization strategies for genotype imputation accuracy in low-coverage whole-genome sequencing of Scylla paramamosain - Weiren Zhang; Lin Chen; Yijia Shih; Peitan Jia; Siyi Zhou; Qionghui Qin; Yaodong Zhang; Kewei Huang; Gongyi Lin; Xiaopeng Wang; Haihui Ye (Aquaculture, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Human umbilical cord MSC-derived exosomes attenuate radiation-induced pulmonary fibrosis via remodeling the gut-lung axis in mice - Yan Zhou; Haonan Wang; Ling Guo; Xiaodie Liu; Xing Wang; Yue Liu; Mengjuan Shang; Bo Zheng; Kewei Li; Lin Liu; Jing Li; Guirong Ding (Life Sciences in Space Research, 2026)

Mangrove Transplantation to the North: Carbon Sequestration Capacity—Drivers and Strategies - Kewei Zhou; Yujuan Lv; Yang Gong; Jing Su; Lei Wang; Shengmin Wu; Xi Lin; Qiuying Lai; Yixin Xu; Xingyi Duan (Journal of Marine Science and Engineering, 2025)
Mangroves play a pivotal role in carbon sequestration. To investigate the characteristics and driving factors of carbon sequestration in planted mangrove forests, we focused on planted mangrove forests in Wenzhou City, Zhejiang Province, China. Through a statistical analysis of soil physicochemical properties and plant morphological characteristics, we assessed carbon stock distribution patterns and identified key influencing factors, providing scientific support for the northward expansion of mangroves. The results demonstrated significant differences in soil properties and plant morphological characteristics among different stands (p

A Deep Learning Framework for Parameter Estimation in 1D Marine Ecosystem Model - Ao Li; Kewei Zhao; Weiwei Fang; Chan Shu; Runjie Zhou; Qiuyi Li; Xiaolong Huang; Xiaohong Lei; Menghan Xu; Haoyu Jiang; Lin Mu (Journal of Marine Science and Engineering, 2025)
Marine ecosystems play an increasingly critical role in both global climate regulation and the impacts of anthropogenic activities. Accurate marine biogeochemical numerical models are essential tools for understanding and predicting the complex dynamics of these systems. However, as model complexity increases, so does the number of biological parameters and the uncertainties associated with them, which can substantially affect model performance. Consequently, efficient and reliable parameter estimation has become a key challenge in model development and application. In this study, we proposed a deep learning-based approach for parameter estimation in numerical models, utilizing deep neural networks to capture the complex nonlinear relationships between numerical model input parameters and output variables. A one-dimensional marine ecosystem model is employed as a case study to evaluate the effectiveness of the proposed method. The results demonstrate that (1) the deep learning approach provides an automated and adaptive solution for parameter estimation, significantly improving the efficiency of model calibration in engineering and scientific applications by enabling rapid identification of near-optimal parameter sets; and (2) the deep learning model effectively learns the underlying nonlinear mappings between inputs and outputs. During training, the mean squared error (MSE) loss exhibits a steady decline, with minor fluctuations in the early stages, ultimately converging to a stable value. The predicted parameter combinations show strong agreement with the reference numerical model outputs, yielding correlation coefficients exceeding 0.95.

Molecular dynamics simulation revealing the interactions between toxic aldehydes and starch: A case study of malondialdehyde, 4-hydroxy-2-hexenal, and 4-hydroxy-2-nonenal in starch-based food during frying - Feng Wang; Xianhong Bi; Yun Cui; Kewei Lin; Charles Brennan; Soottawat Benjakul; Gengsheng Xiao; Lukai Ma (Food Chemistry, 2025)

The aroma profiles of dried gonggans: Characterization of volatile compounds in oven-dried and freeze-dried gonggan - Dongjie Liu; Qiaomei Shen; Kewei Lin; Feng Wang; Zhibin Bu; Jian Peng; Charles Brennan; Soottawat Benjakul; Gengsheng Xiao; Lukai Ma (Food Research International, 2024)

Efficient solar-driven ammonia decomposition using economical K-Co3Mo3N catalyst at low temperatures - Qi Xia; Kewei Ma; Zihan Lin; Congwei Wang; Jianwei Nai; Weiya Jin; Chen Chen (Chemical Engineering Journal, 2024)

Metabolomic analysis reveals the effect of ultrasonic-microwave pretreatment on flavonoids in tribute Citrus powder - Feng Wang; Kewei Lin; Qiaomei Shen; Dongjie Liu; Gengsheng Xiao; Lukai Ma (Food Chemistry, 2024)

Ultrathin-FeOOH-coated MnO2 nanozyme with enhanced catalase-like and oxidase-like activities for photoelectrochemical and colorimetric detection of organophosphorus pesticides - Maoding Zuo; Yuncong Yang; Su Jiang; Chenyu Zhu; Yun Han; Juan Hu; Kewei Ren; Lin Cui; Chun-Yang Zhang (Food Chemistry, 2024)

Zinc-a2-Glycoprotein Acts as a Component of PNN to Protect Hippocampal Neurons from Apoptosis - Kewei Chang; Liyan Lin; Tingting Cui; Hao Zhao; Jiaxin Li; Chang Liu; Dan Gao; Shemin Lu (Molecular Neurobiology, 2024)

The seasonal variability of future evapotranspiration over China during the 21st century - Shan Lin; Xiangyang Sun; Kewei Huang; Chunlin Song; Juying Sun; Shouqin Sun; Genxu Wang; Zhaoyong Hu (Science of The Total Environment, 2024)

Efficacy of a porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) natural recombinant against a heterologous PRRSV-1 isolate both clustered within the subgroup of BJEU06-1-like isolates - Chen Li; Shuai Li; Shubin Li; Ming Qiu; Hong Lin; Zhe Sun; Yuejia Qiu; Wenhao Qi; Binghui Feng; Jixiang Li; Wanglong Zheng; Xiuling Yu; et al. (Veterinary Microbiology, 2023)

Critical Roles of Protein Arginine Methylation in the Central Nervous System - Kewei Chang; Dan Gao; Jidong Yan; Liyan Lin; Tingting Cui; Shemin Lu (Molecular Neurobiology, 2023)

A high-efficient anisotropic continuum model for the optimization of heat transfer and chemical reaction in a packed-bed water gas shift reactor - Bo Jiang; Haonan Wang; Kewei Yu; Jing Ma; Wang Si-ma; Yuming Gao; Lin Li; Xinwei Zhang; Huiru Cui; Dawei Tang (Fuel, 2023)

Glibenclamide Directly Prevents Neuroinflammation by Targeting SUR1-TRPM4-Mediated NLRP3 Inflammasome Activation In Microglia - Yihua He; Yuan Chang; Yuqin Peng; Juan Zhu; Kewei Liu; Jiancong Chen; Yongming Wu; Zhong Ji; Zhenzhou Lin; Shengnan Wang; Sohan Gupta; Nailiang Zang; et al. (Molecular Neurobiology, 2022)

Seasonal prediction of daily PM2.5 concentrations with interpretable machine learning: a case study of Beijing, China - Yafei Wu; Shaowu Lin; Kewei Shi; Zirong Ye; Ya Fang (Environmental Science and Pollution Research, 2022)

Effect of freeze–thaw cycles on volumetric and water retention property of a clay under three compaction conditions - Jianguo Lin; Weilie Zou; Kewei Fan; Haoze Jia; Guitao Zhao (Arabian Journal of Geosciences, 2022)

Characterization and identification of SFDC ‐1, a novel AmpC ‐type β‐lactamase in Serratia fonticola - Xu Dong; Peiyao Zhang; Kexin Zhou; Jialei Liang; Qiaoling Li; Xueya Zhang; Danying Zhou; Wei Lu; Zhewei Sun; Hongmao Liu; Junwan Lu; Xi Lin; et al. (Environmental Microbiology, 2021)
Summary The clinical and environmental infections caused by AmpC β‐lactamases have been increasingly reported recently. In this study, we characterize the novel chromosome‐encoded AmpC β‐lactamase SFDC‐1 identified in Serratia fonticola strain R28, which was isolated from a rabbit raised on a farm in southern China. SFDC‐1 shared the highest amino acid identity of 79.6% with the functionally characterized AmpC β‐lactamase gene bla YRC‐1 , although it had highly homologous functionally uncharacterized relatives in the same species from different sources, including some of the clinical significance. The cloned bla SFDC‐1 exhibited resistance to a broad spectrum of β‐lactam antibiotics, including most cephalosporins with the highest resistance to ampicillin, cefazolin and ceftazidime, with increased MIC levels ≥128‐fold compared with the control strains. The purified SFDC‐1 showed catalytic activities against β‐lactams with the highest catalytic activity to cefazolin. The genetic context of bla SFDC‐1 and its relatives was conserved in the chromosome, and no mobile genetic elements were found surrounding them.

Correction to: XG-PseU: an eXtreme Gradient Boosting based method for identifying pseudouridine sites - Kewei Liu; Wei Chen; Hao Lin (Molecular Genetics and Genomics, 2021)

XG-PseU: an eXtreme Gradient Boosting based method for identifying pseudouridine sites - Kewei Liu; Wei Chen; Hao Lin (Molecular Genetics and Genomics, 2020)

The synthesized transporter K16APoE enabled the therapeutic HAYED peptide to cross the blood-brain barrier and remove excess iron and radicals in the brain, thus easing Alzheimer’s disease - Zhenyou Zou; Qiqiong Shen; Yanxia Pang; Xin Li; Yongfeng Chen; Xinjuan Wang; Xinhua Luo; Zhongmin Wu; Zhaosheng Bao; Juanli Zhang; Jiawei Liang; Lingjia Kong; et al. (Drug Delivery and Translational Research, 2019)

Hepatic apoptosis can modulate liver fibrosis through TIMP1 pathway - Kewei Wang; Bingliang Lin; John J. Brems; Richard L. Gamelli (Apoptosis, 2013)